Implementación del sistema de gestión de seguridad y salud en el trabajo en base a la legislación nacional y la OHSA 18001 en el proyecto de supervición... - Guevara Ramos, Enen Dudley (2014)
The present investigation takes as an aun the implementation of the Safety system and health in the work on the basis of the National Legislation and the Ohsa 18001, for the provision of services, which allows the constant adjustment of the organization the changes of the environment and the increasing needs of the clients and interested parts, as well as the model employment and management tools to measure his behavior. The scientific approached problem expresses that " The Company " CESEL S.A " that offers the service of Supervision in the Proj ect of of the Balance of the Work of Rehabilitation and Improvement of the Road Trujillo - Shiran - Huamachuco 2014, To this respect he needs from a model of management, that it allows to see her in an integral way, where the aims and indicators pay to the global strategy, the constant improvement of the processes is guaranteed and the repetition of the information is avoided, the human mistakes and incongruities, to promote a culture of prevention of incidents and occupational accidents in our workers ".